Screen distractions during Memrise MALL experience: Course-of-action study on students’ performance and perception - Azwar Abidin (UNIB Press, 2023)
This study employed Course-of-Action methodology in a mixed-methods approach to examine the impact of screen distractions on Memrise MALL experience in an EFL flipped classroom setting. An Exploratory Sequential Design was utilized to analyze the two-week Memrise MALL experience and its impact on the screen behaviors of 46 Indonesian first-year university students. Descriptive and nonparametric inferential statistics were employed to analyze the quantitative data, while confrontative interview data were transcribed and encoded using in vivo coding to mark key phrases in the participants' comments. Results of the study indicated that social media and entertainment apps were the most common type of distraction and that these distractions had a detrimental effect on task performance. The participants expressed their appreciation for the customizable learning experience and found the app layouts and gamification features were encouraging; however, they found it challenging to switch between multiple tabs or windows on a mobile screen. There was a small correlation between total screen distractions and total vocabulary learned, as well as a strong correlation between total screen distractions and the total time spent on the task.